Systematic Review of Clinical Governance Models in Indonesian Hospitals: Implications for Patient Safety and Risk Management - Jihan Eka Ariyani (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This study aims to systematically examine the application of the clinical governance model in Indonesian hospitals and its implications for patient safety and risk management. The study was conducted using a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines. A literature search through PubMed, Scopus, and Google Scholar yielded 527 articles, and 21 articles met the inclusion criteria for thematic analysis. The results show that the implementation of Clinical Governance in Indonesia has included clinical audits, incident reporting, and competency enhancement of health workers, but the integration of clinical leadership aspects, safety culture, and risk management is still not optimal. Factors supporting success include leadership commitment, institutional policies, and effective reporting systems, while obstacles include limited human resources and lack of an integrated quality system. In conclusion, Clinical Governance plays an important role in improving patient safety and risk management effectiveness. Consistent implementation, policy support, and capacity building of health workers are needed to realize sustainable and quality clinical governance in Indonesian hospitals.